Rancang Bangun Aplikasi Cerdas Menentukan Bakat Anak Dengan Teorema Bayes Berbasis Android - Hasugian, Penda Sudarto; Simbolon, Liber (MEANS (Media Informasi Analisa dan Sistem), 2020)
All children are born with unique personalities and talents, and of course, parents want to always give the best for their children, such as a place to play, clothing, food and education. In terms of education, there are still many parents who do not see what their children want or like to learn and what their children don't enjoy. But parents impose a desire on their child to learn a subject that the child does not select or want so that the child tends to be forced to learn and results in not optimal results. This problem is the background for making smart applications to determine children's talents with the Android-based Bayes theorem based on early childhood personality. This intelligent application built on an Android basis with the Bayes theorem can help parents or the general public to find out the talents of each child from an early age. So that education, the lessons that will be taken by a child are appropriate and have qualified skills. This type of research is a development research category, namely producing application products that can be used by the general public, the research process involves experts in the field of psychology by way of direct communication to create data used in determining children's talents from an early age.